Trends in Problem Based Learning Model Based on Lesson Study on Learning Outcomes: A Bibliometric Analysis - Aisyah Rehan Fadhillah Fadhillah; Annisa Fadhilaturrahmi; Rofifah Widara; Asrizal Asrizal; Mutiara Nurul Fitri (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
Twenty first century education focuses on developing critical skills, creativity, collaboration, and communication, utilizing digital technology and innovative learning models. This study aims to evaluate the effectiveness of a problem-based learning (PBL) model based on lesson study in improving student learning outcomes. This research uses bibliometric analysis method, examining the literature from 2019-2024 with Publish or Perish and VOSviewer tools. The results showed that research on lesson study-based PBL in learning is still a relatively new and promising area. Network visualization and keyword density show that this topic has potential for further development. Recent trends show that the integration of PBL and lesson study can improve students' conceptual understanding and practical skills, and address low learning outcomes. This research highlights the importance of implementing innovative learning models to support the improvement of learning quality and student learning outcomes in a broader context.